Evaluation of antioxidating activity of tea maked in free fairs and industrialized tea in San Luís-Maranhão, Brazil (Research, Society and Development, 2020)
The benefits bring benefits to the body due to its antioxidant, anti-inflammatory and antimutagenic properties. The antioxidant activity of teas marketed in open markets and industrialized teas in São Luís - MA was evaluated. After the use of Lemon Balm (Melissa officinalis), Bilberry (Peumus boldus), Chamomile (Matricaria chamomilla) and Mint (Mentha) teas by decoction process after liquid-liquid extraction with ethyl chemical reagent (FAE). An antioxidant activity was performed by the DPPH method, which is an organic compound 2,2-diphenyl-1-picrylhydrazyl, where it was used in the analysis of 31.25 to 500 μg/mL of each tea extract. The extracts with the best antioxidant activity were inoculated in tenebrous molybdenum larvae (100 and 200 µg/mL) to test toxicity and protection against oxidative stress induction.The FAE of chamomile and industrial boldo tea has antioxidant activity of 60 and 50% (p